Adaptation - Jonze, Spike; Kaufman, Charlie, 1958-; Kaufman, Donald; Saxon, Edward; Landay, Vincent; Cage, Nicolas, 1965-; Streep, Meryl; Cooper, Chris, 1951-; Orlean, Susan; Columbia Pictures; Intermedia Films (London : Columbia Tristar Home Entertainment, 2003)
A lovelorn screenwriter becomes desperate as he tries and fails to adapt 'The Orchid Thief' by Susan Orlean for the screen.
Film -- Filmographies -- Trailers.
Originally released as a motion picture in 2002.
Nicolas Cage, Meryl Streep, Chris Cooper.
Suitable only for persons of 15 years and over.
Suitable only for persons of 15 years and over.
DVD ; PAL, region 2 ; aspect ratio, anamorphic widescreen ; Dolby digital surround 5.1.
English dubbed into Italian with English, Hindi, and Italian subtitles. English for the hearing impaired.
Keywords: Motion pictures -- United States; Feature films